Research of corporate compliance in China: Review and reflections - Li, Bencan (International journal of law, crime and justice, 2022)
This article sorts out the research from the past decade on corporate compliance in China. Chinese scholars have studied corporate compliance from different disciplines and perspectives. In terms of research methods, the study of corporate compliance should adopt the dogmatics approach to provide a stable theoretical framework for the construction of the compliance system. In terms of research direction, future research needs formal thinking to delimit the institutional boundaries of criminal compliance. As for unit imputation mode, corporate compliance does not solely depend on any certain mode. No vicarious responsibility, strict responsibility or organizational responsibility constitutes the institutional foundation of compliance. Before China's legislation is amended, compliance should serve as a factor to exclude or reduce corporate responsibility so as to encourage corporate compliance.